2020
DOI: 10.1080/15732479.2020.1833046
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian inference approach for the updating of spatially distributed corrosion model parameters based on heterogeneous measurement data

Abstract: In many countries concrete bridges are reaching the end of their service-life, showing signs of deterioration, e.g. due to corrosion. Hence, the question arises whether their safety level is still acceptable. To improve the estimate of the safety level, information extracted from different tests, e.g. proof-loading, operational modal analysis, etc., where deflections, strains or accelerations are measured, can be used. Unfortunately, in practice inspection results are often not used directly to improve our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…These can include visual observations, static strain or deflection measurements, dynamic tests resulting in modal data, destructive measurements, etc. (Vereecken et al, 2021). In this work, the focus was on static strain data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These can include visual observations, static strain or deflection measurements, dynamic tests resulting in modal data, destructive measurements, etc. (Vereecken et al, 2021). In this work, the focus was on static strain data.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement results (i.e. static strain data) are generated based on a finite element model of the beam as described in (Vereecken et al, 2021), and this for the different correlation models. The load applied to the beam consists of a point load of 30 kN at midspan.…”
Section: Influence Of the Correlation Model On The Posterior Distribu...mentioning
confidence: 99%
See 2 more Smart Citations
“…When designing a structure with respect to robustness, it must also be taken into consideration that progressive collapses caused by extreme events are low-probability high-consequence phenomena [1]. In order to be able to accurately predict the structural response, it is important to study the progressive collapse behavior using a probabilistic approach, as it has been found that there is a significant influence of many uncertainties on the structural behavior, e.g., randomness from material properties, which is neglected by most existing studies [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, in the three widely used approaches in relation to the quantification of the structural robustness, i.e., deterministic-based method, probabilisticbased method, and risk-based method [30,43,44], both the probabilistic-based method and the risk-based method require a reliability analysis.…”
Section: Introductionmentioning
confidence: 99%